Integrated environmental management model of air pollution control by hybrid model of DPSIR and FAHP - M.J. Mohammadizadeh; A.R. Karbassi; Gh.R. Nabi Bidhendi; M. Abbaspour (Global Journal of Environmental Science and Management)
The aim of this study is to evaluate the obstacles due to a DPSIR model combined with fuzzy analytic hierarchy process technique. Hence, to prioritize the responses regarding the driving forces, pressures, states and impacts, the hierarchy of the model is established. Evaluations and prioritization of model results of urban transport situation in Tehran have provided a number of necessary issues for strategic planning to reduce local air pollution and emission of greenhouse gases by prioritizing their effectiveness in the implementation, including; a) development and improvement of public transport (R1), b) improvement of fuel quality (R2), c) improvement of vehicle emission standards (R3), d) vehicle inspection (R4), f) traffic management (R5). In this study, responses to improve the factors of pressure, stimulus, the current state and the impacts were examined and compared hierarchically. Finally, their priority relative to each other was achieved. Development and improvement of public transport, improvement of the quality of fuel, improvement of vehicle emission standards, vehicle check-up and finally urban traffic management were identified respectively as practical steps to control and reduce air pollution in Tehran.